Risk factors assessment of bovine tuberculosis among abattoir personnel in Barishal City of Bangladesh - Anower, AKM Mostafa; Sayed, Abu; Tamal, Aninda Kundu; Ansari, Wahedul Karim; Arafat, Md Yeasin (Asian Journal of Medical and Biological Research, 2023)
Bovine tuberculosis (bTB), caused by Mycobacterium bovis, is a chronic zoonotic, contagious as well as notifiable disease which results in significant economic damages and poses a serious threat to public health. Hence, this study was undertaken and carried out from July 2022 to June 2023 among the abattoir workers in Barisal City Corporation area to assess the degree of comprehension, attitudes, and practices concerning bTB prevention and control as well as awareness of public health. A total of 50 abattoir personnel participated in the study. A pre-tested questionnaire was developed for the face to face interview of the participants. Descriptive analysis and chi-square test were employed to determine the strength of association of education and training status with the awareness as well as the knowledge regarding bTB prevention and control of the abattoir personnel using SPSS, Version 25. This study demonstrated that abattoir workers who received training on meat handling and processing have a good understanding of disinfection of the meat preparing place and equipment for ensuring food safety and preventing bacterial contamination. There was a statistically significant association between respondents’ awareness of bTB and their training status. However, the study revealed inadequate knowledge amongst both trained and non-trained abattoir personnel pertaining to issues of public health, bTB transmission, prevention and control. Therefore, it is strongly recommended that the relevant authorities should take necessary steps to ensure regular training and educational programs on meat handling and processing for prevention and control of bTB as well as other zoonotic diseases in order to protect public health. Asian J. Med. Biol. Res. 2023, 9 (3), 97-105